"Green Stimulus," Economic Recovery, and Long-Term Sustainable Development - Strand, Jon; Toman, Michael (World Bank, Washington, DC, 2014)
This paper discusses short-run and long-run effects of "green stimulus" efforts, and compares these effects with "non-green" fiscal stimuli. Green stimulus is defined here as short-run fiscal stimuli that also serve a "green" or environmental purpose in a situation of "crisis" characterized by temporary under-employment. A number of recently enacted national stimulus packages contain sizeable "green" components. The authors categorize effects according to their a) short-run employment effects, b) long-run growth effects, c) effects on carbon emissions, and d) "co-benefit" effects (on the environment, natural resources, and for other externalities). The most beneficial "green" programs in times of crisis are those that can stimulate employment in the short run, and lead to large "learning curve" effects via lower production costs in the longer term. The overall assessment is that most "green stimulus" programs that have large short-run employment and environmental effects are likely to have less significant positive effects for long-run growth, and vice versa, implying a trade-off in many cases between short-run and long-run impacts. There are also trade-offs for employment generation in that programs that yield larger (smaller) employment effects tend to lead to more employment gains for largely lower-skilled (higher-skilled) workers, so that the long-term growth effects are relatively small (large). Ultimately, the results reinforce the point that different instruments are needed for addressing different problems.